Theoretical Model for Predicting Moisture Ratio during Drying of Spherical Particles in a Rotary Dryer. (4th June 2013) - Ademiluyi, F. T.; Abowei, M. F. N.
Abstract : A mathematical model was developed for predicting the drying kinetics of spherical particles in a rotary dryer. Drying experiments were carried out by drying fermented ground cassava particles in a bench scale rotary dryer at inlet air temperatures of 115–230°C, air velocities of 0.83 m/s–1.55 m/s, feed mass of 50–500 g, drum drive speed of 8 rpm, and feed drive speed of 100 rpm to validate the model. The data obtained from the experiments were used to calculate the experimental moisture ratio which compared well with the theoretical moisture ratio calculated from the newly developed Abowei-Ademiluyi model. The comparisons and correlations of the results indicate that validation and performance of the established model are rather reasonable.